2006
DOI: 10.1002/ana.20933
|View full text |Cite
|
Sign up to set email alerts
|

Progressive multifocal leukoencephalopathy revisited: Has the disease outgrown its name?

Abstract: Nothing is more disappointing for patients than when a promising new treatment hits a roadblock because of unexpected side effects. This is what happened when natalizumab (Tysabri) was associated with a few cases of progressive multifocal leukoencephalopathy (PML) in multiple sclerosis and Crohn's disease patients, caused by the reactivation of the polyomavirus JC. These dramatic events drew PML squarely into the spotlight and generated considerable interest from the medical community, the pharmaceutical indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
211
0
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(223 citation statements)
references
References 110 publications
5
211
0
7
Order By: Relevance
“…Furthermore, they also show that an efficient and selective inhibition of T cell accumulation in the brain of MS patients is likely sufficient to retard or halt the disease course, and thus underscore the notion that autoreactive CD4 ϩ T cells within the CNS represent the trigger of the disease (1). We did not directly investigate the reason for the development of PML as a rare side effect of natalizumab treatment, but it has been shown that that the cellular immune response by CD4 ϩ and CD8 ϩ T cells is critically required to contain JC virus infection (29). Therefore, we speculate based on our results that inefficient immune surveillance of the CNS by T cells facilitates the replication of JC virus.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, they also show that an efficient and selective inhibition of T cell accumulation in the brain of MS patients is likely sufficient to retard or halt the disease course, and thus underscore the notion that autoreactive CD4 ϩ T cells within the CNS represent the trigger of the disease (1). We did not directly investigate the reason for the development of PML as a rare side effect of natalizumab treatment, but it has been shown that that the cellular immune response by CD4 ϩ and CD8 ϩ T cells is critically required to contain JC virus infection (29). Therefore, we speculate based on our results that inefficient immune surveillance of the CNS by T cells facilitates the replication of JC virus.…”
Section: Discussionmentioning
confidence: 86%
“…However, surprisingly, JCV PCR was positive in only 24 % of patients with radiology findings suggestive of PML (Table 1). This low detection rate may be due to non-specificity of radiological findings (Antinori et al, 1997) or insensitivity of PCR, or perhaps due to highly active antiretroviral therapy (HAART) re-establishing host immune function and reducing JCV below detectable levels (Koralnik, 2006). These possibilities are supported by the findings that PML is often difficult to distinguish radiographically from lesions caused by HIV encephalopathy (Olsen et al, 1988;Koralnik et al, 1999) and that the sensitivity of JCV PCR dropped from 89.5 % in the pre-HAART era (1992)(1993)(1994)(1995) to 57.5 % in the HAART era (1996)(1997)(1998)(1999)(2000)(2001)(2002) (Marzocchetti et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of highly active antiretroviral therapies (HAART) has increased the mean survival time of AIDS patients with PML from 2 months to one year but has had no effect at reducing the overall incidence of PML in the HIV infected population (Koralnik, 2006). Recently, PML emerged in two multiple sclerosis patients undergoing treatment with IFNβ-1a (Avonex) and Natalizumab (Tysabri) and one Crohn's disease patient undergoing treatment with Natalizumab (Tysabri) (Berger and Koralnik, 2005;Kleinschmidt-DeMasters and Tyler, 2005;Langer-Gould et al, 2005;Van Assche et al, 2005).…”
Section: Discussionmentioning
confidence: 99%